Matematika Dalam Al-Qur'an: Belajar Sambil Tafakkur? - M. Imamuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to explore and uncover hidden mathematical patterns and phenomena in the structure of the Qur'ān, which have often only been understood from the spiritual and legal dimensions. Using a qualitative approach and textual analysis of the Qur'ān, the researcher analyzed the word order, frequency of occurrence, and relationships between verses. The analysis was carried out on the balance of the words